2014
DOI: 10.1007/s13277-014-2913-x
|View full text |Cite
|
Sign up to set email alerts
|

The negative regulators of Wnt pathway—DACH1, DKK1, and WIF1 are methylated in oral and oropharyngeal cancer and WIF1 methylation predicts shorter survival

Abstract: The deregulation of Wnt signaling has recently emerged as one of the drivers of head and neck cancers. This is frequently related to the methylation of several antagonists of this pathway. This study aimed at the assessment of the profile of methylation of Wnt pathway antagonists and the determination of the prognostic value of the methylation of selected genes in oral carcinomas. The methylation of DACH1, DKK1, LKB1, PPP2R2B, RUNX3, SFRP2, and WIF-1 was analyzed in 16 oral squamous cell carcinoma cell lines u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 38 publications
(56 reference statements)
1
36
0
2
Order By: Relevance
“…In accordance, Padhi et al reported of a correlation between β-cat expression and poor prognosis in head and neck cancer [12] in vivo . This is supported by the very recent finding that inactivation of several Wnt inhibitors through methylation is frequently found in oral cancer, correlating with a shorter survival [13]. The association of aberrant Wnt signaling to e.g.…”
Section: Introductionmentioning
confidence: 70%
“…In accordance, Padhi et al reported of a correlation between β-cat expression and poor prognosis in head and neck cancer [12] in vivo . This is supported by the very recent finding that inactivation of several Wnt inhibitors through methylation is frequently found in oral cancer, correlating with a shorter survival [13]. The association of aberrant Wnt signaling to e.g.…”
Section: Introductionmentioning
confidence: 70%
“…Dysregulation of the Wnt signaling pathway can promote the progression of oral cancer and is significantly associated with prognosis in patients with OSCC . Epigenetic silencing by DNA methylation of Wnt antagonists is frequently detected in oral cancer and is considered a prognostic marker . Lee et al have showed a significant association between EGFR expression and aberrant accumulation of β‐catenin in oral cancer, suggesting EGFR signaling regulates β‐catenin localization and stability.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this finding, we observed inhibition of ERK phosphorylation in HNSCC following treatment with 80 μg/ml RA ( Figure 2C). However, it is important to note that there are a number of signaling pathways, in addition to the MAPK/ERK pathway, that are responsible for cell proliferation and survival in HNSCC, such as Wnt [47] and JAK/STAT [48,49] signaling. Given the relative paucity of information in the literature describing the effects of RA on tumor cell signaling, next steps in our laboratory will focus on elucidating parallel signaling cascades and upstream receptors that might also be targeted by RA in HNSCC.…”
Section: Discussionmentioning
confidence: 99%